Vitamin D3 effect on Albuminuria in Type 2 Diabetes Mellitus patients in Northern Andhra Pradesh, India - Dr. P. Sreedevi; Dr. B. Annaji; Dr. K. Sudheer; Dr. Tammineni Venugopal (International Journal of Medical Research and Review, 2020)
Introduction: Vitamin D deficiency is a common disorder in diabetic patients and may be a risk factor for the progression of diabetic nephropathy. The present study aimed to assess the effects of a large dose of parenteral. Vitamin D on 24 hours albuminuria in T2DM patients.Methods: This prospective single-center study included 80 vitamin D deficient [25(OH) D <50 nmol/l] T2DM patients with an adequate glycemic control (HbA1c< 7.0%). Without any changes in anti-hyperglycemic or antihypertensive drugs, these patients were given a single high dose (600000 IU) of parenteral Vitamin D3. Then the changes in Vitamin D levels and 24 hours albuminuria were seen on follow up at 3 months.Results: Vitamin D3 supplementation improved 24 hours albuminuria. In the present study, Twenty-four-hour urinary albumin excretion decreased from 210.4 ± 101.2 to 204.6 ± 104.5. In males, it changed from 221.8 ± 99.7 to 216.1 ± 100.3 and in females, it changed from 192.3 ± 108.5 to 186.7 ± 113.1. There was a negative association of albuminuria with Vit D levels in the present study.Conclusion: Vitamin D3 supplementation significantly reduces 24-hour urinary albumin excretion in T2DM patients with Vitamin D3 deficiency.